Insulin Delivery Method and Admission for Glycemic Control in Pregnant Women with Type 1 Diabetes Mellitus - Sperling, Jeffrey D.; Maggio, Lindsay; Has, Phinnara; Daley, Julie; Coustan, Donald R.; Werner, Erika F. (American Journal of Perinatology, 2018)
Objective To determine if there was a difference in glycemic control admissions or perinatal outcomes in women with type 1 diabetes mellitus (DM) treated with multiple daily injections (MDIs) versus continuous subcutaneous insulin infusion (CSII).Materials and Methods This was a retrospective cohort study of women with type 1 DM with a singleton gestation who delivered between 2006 and 2014 at a tertiary hospital and received care at a dedicated DM clinic. Women who used MDI were compared with those who used CSII. The primary outcome was glycemic control admission during pregnancy. Secondary outcomes included adverse perinatal outcomes.Results There were a total of 156 women; 107 treated with MDI and 49 with CSII. Women treated with MDI had higher rates of glycemic control admissions versus those treated with CSII (68.2 vs. 30.6%, p < 0.001). Adjusting for age, ethnicity, public insurer, duration of DM, first recorded hemoglobin A1c (HbA1c), and DM comorbidities, the likelihood of admission remained higher in women on MDI versus CSII (AOR 5.9 [1.7–20.6]). Women treated with MDI had higher rates of postprandial hypoglycemia. Other perinatal outcomes were similar between the groups.Conclusion Women with type 1 DM treated with MDI were more likely to have glycemic control admissions and postprandial hypoglycemia than those treated with CSII.
Keywords: type 1 diabetes mellitus; CSII; glycemic control; continuous subcutaneous insulin infusion; multiple daily injections; insulin; pregnancy